Hierarchical MoS2/MoO3 nanotubes with excellent electrochemical performance: MoS2 bubbles on MoO3 nanotubes. Issue 44 (29th October 2019) - Ma, Ying; Jia, Yulong; Lin, Yinhe; Shi, Wenbing
Abstract : Hierarchical MoS2 /MoO3 nanotubes consisting of bubble-like hollow MoS2 nanospheres and MoO3 nanotubes were fabricated with excellent electrochemical performance. The growth mechanism of hierarchical MoS2 /MoO3 nanotubes was proposed. Abstract : In this study, hierarchical MoS2 /MoO3 nanotubes are fabricated through an elegant method. MoO3 nanorods serve as not only growth templates but also Mo precursors. It is well established that bubble-like MoS2 hollow nanospheres are uniformly distributed on the MoO3 nanotubes. Ascribed to the unique architecture and synergistic effect of active materials, the as-prepared hierarchical MoS2 /MoO3 nanotubes exhibit excellent electrochemical performance for energy storage. This work sheds light on the design of hybrid hierarchical nanotubes as electrochemical electrode materials through an elegant and feasible strategy, providing an idea for fabricating hybrid materials with a high capacitive ability.